Adsorption of Oxalic Acid onto Hematite: Application of Surface Potential Measurements - Tajana Preočanin; Željka Majić; Davor Kovačević; Nikola Kallay (Adsorption Science & Technology)
The surface potential at the hematite/aqueous oxalic acid interface was measured by means of a hematite Single Crystal Electrode. This allowed the simultaneous interpretation of the surface potential, electrokinetic potential and adsorption data for the adsorption of oxalic acid onto a hematite surface. Based on the Surface Complexation Model, this interpretation suggested that the oxalate ion is bound to a metal ion at the solid surface to form a singly-charged oxalate-surface complex, with the charge being exposed to the potential at the outer Helmholtz layer. A number of equilibrium parameters describing the interfacial equilibrium were obtained. Thus, for the two protonation steps of the surface sites, the thermodynamic equilibrium constants were log K 1 = 7.1 ± 0.4 and log K 2 = 5.2 ± 0.4, respectively. Two assumptions were tested with regard to the adsorption equilibrium constant, i.e. the charge of the surface complex is exposed to the inner surface potential, ψ 0 , or to the outer surface potential, ψ d . The constancy of the interfacial equilibrium constants led to the conclusion the latter assumption was the more appropriate. The observed value of the adsorption equilibrium constant was log K ads = 3.0 ± 0.8. It was shown that measurement of the surface potential by Single Crystal Electrodes is a helpful tool in elucidating the equilibrium behaviour of the complex at the interface.